Penerapan Good Corporate Governance dalam Manajemen Risiko Bank Perkreditan Rakyat Syariah - Nurid Fadhilatul B. M; Nurul Hanani; Sri Dwi Estiningrum (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Management of Sharia finance company is based on good corporate governance principle. It’s principle applied to manage company operational and kept sharia finance company among the bankings competition. Its company activities has many risks indeed. Since company as funding and financing party, so its confront the vital risk. Because of that, its has good risk management needed. Moreover, in the risk of financing. The risk management on the sharia finance company based on the sharia banking’s regulation. Its regulation include of Good Corporate Governance principle and Risk Management principle. For having to know this application is research carefully on the sharia finance company of BPRS Lantabur Tebuireng.This research makes use of qualitative approach with collecting data methods are observation, interview and documentation. Analysis process in this research are data reduction, description, makes conclusion and the last is data’s validity checking.The research result shows that application of good corporate governance (GCG principle) in the risk management of BPRS Lantabur Tebuireng’s financing are good. Amount four aspect of Good Corporate Governance (GCG) principle were good application are transparency, accountability, responsibility, and fairness. Meanwhile, one aspect of Good Corporate Governance (GCG) principle were bad application (not effective) is independency. Its independency aspect on the financing’s decision making is not effective yet. By the result of that, BPRS Lantabur Tebuireng needs good management process to cover financing analysis from customers financing propose.